PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN KRL COMMUTERLINE DI KEBAYORAN LAMA - Lucy Nancy Simatupang (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2016)
Singer study aims to determine how the Effect QUALITY review Service Customer Satisfaction KRL Commuterline in Kebayoran Station. Population Research hearts Singer Was All users Train Station Commuterline in Kebayoran Lama. Searching Google Articles 45 Passengers taking samples, sampling methods accidental WITH collecting data using questionnaires, while the measurement of the variables which are used scale you Likkert WITH five stretches. Methods Data Testing done is test the reliability and validation. Methods of Data Analysis Performed: Correlation analysis, Classical Assumption Test, Multiple Linear Regression Analysis, t test and f test and coefficient of determination (R2). Research shows that physical evidence, Responsiveness and Assurance NOT have an influence KRL Customer Satisfaction Commuterline while reliability and empathy has influence KRL Commuterline Customer